DESCRIPTION OF NUTRITIONAL STATUS CHILDREN OF PRIMARY SCHOOL AGE AT AL-CHUSNAINI ISLAMIC ELEMENTARY SCHOOL KLOPOSEPULUH SUB-DISTRICT SUKODONO DISTRICT - Khuyyizatul Salsabilah, Khuyyizatul Salsabilah; Loetfia Dwi Rahariyani; Dony Sulystiono (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Nutrition is one of the foundations for public health, if there are disturbances of malnutrition, undernutrition, excess nutrition, and obesity growth will not take place optimally. Lack of nutrients results in reduced comprehension, physical growth is not optimal, stature tends to be short, not active, while excess nutrients will increase the risk of degenerative diseases in the future. This study aims to describe the nutritional status of elementary school-age children at Al-Chusnaini Islamic Elementary School, Kloposepuluh Subdistrict, Sukodono District. This research method is a descriptive study. The population and sample size are the same, namely 50 grade 1 students and 50 grade 2 students. The data for this study were taken by measuring height and weight and then calculated based on body mass index (BMI) and Z-Score. The results of the study showed that almost all students in grades 1 and 2 were in the good nutrition category, nutritional status was seen by gender, it was found that male students experienced more obesity problems, while female students experienced more malnutrition problems. This research is expected to be a reference in monitoring the nutritional status of elementary school students as well as a reminder for teachers to teach students how important it is to have good nutritional status, eat according to balanced nutrition guidelines, and actively participate in sports activities that have been facilitated by the school.